Application of input shaping control strategy for reducing chatter noise in the automotive wiper system - Ahmad, A. (IEEE, 2008)
Chatter is one of the unwanted noises generated during wiper operation. It is a low frequency and selfexcited vibration that is often generated before and after the wiper reverses direction. This leads to poor visibility and an annoying sound to the driver and passengers. This paper intends to propose a control technique that is capable of reducing chatter noise and vibration in the automotive windshield wiper system. In doing so, an existing two-dimensional mathematical model of a wiper system is adopted. MATLAB Simulink is then used to simulate vibration response of the wiper. The simulated results are then verified by those obtained in the experiment. With the verified model, a control strategy, namely, input shaping is introduced. It is found that input shaping technique can reduce vibration level by approximately 30 percents over the model without control scheme.